PRESCRIBING IN GERIATRIC HYPERTENSIVE PATIENTS IN THE INPATIENT INSTALLATION OF RSUD R. SYAMSUDIN, S.H. SUKABUMI CITY - Levina Geby Dwi Putri Alamsyah; Umi Yuniarni; Fetri Lestari (Bandung Conference Series: Pharmacy, 2023)
Abstract. Geriatric patients are elderly patients with various diseases and / or diseases caused by physical, psychological, social, economic disorders and also experience a decrease in physiological function due to the degeneration process so that the body is susceptible to diseases and infectious diseases. One of the degenerative diseases that are commonly found in the elderly is hypertension. This study aims to determine the pattern of prescribing in geriatric hypertension patients at the Inpatient Installation of RSUD R. Syamsudin, S.H. including types of drugs, drugs for comorbidities, doses, and routes of administration. This research is a non-experimental research with a retrospective descriptive design. The results showed that the most widely prescribed antihypertensive drug was a single therapy class of Calcium Channel Blocker (CCB), the type of drug used was amlodipine. The composition of hypertensive patients without comorbidities was 75%, with comorbid heart disease by 15.69%, with comorbid diabetes mellitus and gout by 4%, with comorbid asthma by 2%. The most widespread use of antihypertensive drugs is given by monotherapy by 66%, a combination of 2 drugs by 22%, a combination of 3 drugs by 6%, and a combination of 4 drugs by 2%. Abstrak. Pasien geriatri adalah pasien lanjut usia dengan berbagai penyakit dan/atau penyakit yang diakibatkan oleh gangguan fisik, psikologis, sosial, ekonomi dan juga mengalami penurunan fungsi fisiologis akibat proses degenerasi sehingga tubuh rentan terhadap penyakit dan infeksi penyakit menular. Salah satu penyakit degeneratif yang banyak dijumpai pada lansia yaitu hipertensi. Penelitian ini bertujuan untuk mengetahui pola peresepan pada pasien hipertensi geriatri di Instalasi Rawat Inap RSUD R. Syamsudin, S.H. meliputi jenis obat, obat untuk penyakit penyerta, dosis, dan rute pemberian. Penelitian ini merupakan penelitian non eksperimental dengan rancangan deskriftif yang bersifat retrospektif. Hasil penelitian menunjukkan obat antihipertensi yang paling banyak diresepkan yaitu terapi tunggal golongan Calcium Channel Blocker (CCB) jenis obat yang digunakan adalah amlodipine. Komposisi pasien hipertensi tanpa penyakit penyerta sebesar 75%, dengan komorbid penyakit jantung sebesar 15,69%, dengan komorbid diabetes melitus dan asam urat sebesar 4%, dengan komorbid asma sebesar 2%. Penggunaan obat antihipertensi paling banyak digunakan yaitu dengan monoterapi sebesar 66%, kombinasi 2 obat sebesar 22%, kombinasi 3 obat sebesar 6%, dan kombinasi 4 obat sebesar 2%.